Perlindungan Hukum Pekerja Wanita dan Anak - Primahaditya Putra Bintang Adi Pradana (Departemen Ilmu Pemerintahan Fisip Unhas, 2018)
Labor is one of those who take action for employers with assistance for needs, thus everything must be regulated and facilitated related to employment. With female and child labor, which must be done and rules must be agreed upon by the farmer and the child will be employed as labor in a company, In labor activities there are many aspects that are interrelated in it, there are a series of rules for regulating and responding to the existence of female and child labor, in this case we can see in the regulations that are in Law No. 13 of 2003 concerning Employment, all things related to labor contained in the Act. The existence of this regulation is still found by individual companies who commit unlawful acts which are often found in the mass media which illustrate what rules are often applied by companies in the employment arrangements which will be explained in more detail in the discussion of this article.